Calcium and delayed potassium currents in mouse pancreatic beta-cells under voltage-clamp conditions. - Rorsman, P; Trube, G (1986)
Pancreatic islets of NMRI mice were dissociated into single cells which were kept in tissue culture for 1-3 days. The whole-cell configuration of the patch-clamp technique was used to study inward and delayed outward currents of beta-cells under voltage-clamp conditions at 20-22 degrees C. Outward currents were suppressed by substituting the impermeant cation N-methyl-D-glucamine for intracellular K+. The remaining inward current had a V-shaped current-voltage relation reaching a peak value of 39 +/- 4 pA (mean +/- S.E. of mean) around -15 mV. It was identified as a Ca2+ current, because the peak amplitude was increased 1.6 times by increasing external [Ca2+] ([Ca2+]o) from 2.6 mM to 10 mM and it was blocked by Co2+ (5 mM) or nifedipine (5 microM) but not by TTX (20 microM). The activation time constant of the inward current at -10 mV was 1.28 +/- 0.08 ms. The relation between the degree of activation (estimated from the size of the tail currents) and membrane potential V followed the sigmoidal function f = 1/(1 + exp [(Vh-V)/k]) with half-maximal activation potential, Vh = 4 +/- 1 mV and slope factor, k = 14 +/- 1 mV (for [Ca2+]o 10 mM). The inward current inactivated only weakly during depolarizing pulses of 0.1-1 s duration. The delayed outward current (in experiments with 155 mM-internal [K+] ([K+]i)) had a linear voltage dependence at potentials above -20 mV; its amplitude at -10 mV was 210 +/- 30 pA. Tail currents related to the activation of the outward current had K+-dependent reversal potentials. The current was blocked by extracellularly applied tetraethylammonium (20 mM) and 4-aminopyridine (2 mM). It was not affected by glibenclamide (3 microM), tolbutamide (0.2 mM) and alterations of intracellular [Ca2+] (1 nM-1 microM). The activation time constant of the outward current at -10 mV was 21 +/- 3 ms. The voltage dependence of activation could be described by the sigmoidal function (see above) with Vh = 19 +/- 1 mV and k = 5.6 +/- 0.4 mV. The outward current inactivated during long (15 s) depolarizing pre-pulses (time constant at -10 mV: 2.6 +/- 0.6 s). 50% inactivation occurred at Vh = -36 +/- 2 mV, k was -4.1 +/- 0.2 mV. Inward and outward currents during depolarizing voltage pulses in beta-cells are similar to Ca2+ and delayed K+ currents in other cell types. These currents seem sufficient to generate the action potentials of the beta-cell.